Fraud Detection of Financial Statements With Beneish M-Score Kompas100 Company (Empirical Study on the Indonesian Stock Exchange of Kompas100 Company in 2018-2020) - Erwin Febriansyah; Silfi Lestari (Realible Accounting Journal, 2022)
Purpose - The purpose of this study is to determine the percentage of Kompas100 companies on the Indonesia Stock Exchange in 2018-2020, Methods This study uses a qualitative approach. the population in this study were companies listed on the Indonesia Stock Exchange during the period 2018-2020 and the samples used in this study were 15 companies listed on the Indonesia Stock Exchange. Data Analysis Techniques using the Beneish M-Score. The variables in this study are (DSRI), (GMI), (AQI), (SGI), and (TATA). Finding The findings in this study are the 2018 there were 5 companies or 33.3%, in 2019 there were 12 companies or 80%, and in 2020 there were 7 companies or 46.6%, companies classified as non-manipulators had indications of not committing fraud. to financial statements. In 2018 there were 1 or 6.6%, in 2019 there were 0 or 0%, and in 2020 there were 3 companies or 20%, companies classified as manipulators had indications of committing fraud against financial statements. In 2018 there were 9 companies or 60%, in 2019 there were 3 companies or 20%, and in 2020 there were 5 companies or 33.3%, companies that are not classified as non-manipulators and manipulators are included in the gray company category.